Effects of terrains’ soil and altitude on performance of Abyssinian pea (Pisum sativum var. abyssinicum A. Braun) landraces of Ethiopia - BERHANU ABRAHA TSEGAY; Berhane G. Gebreegziabher (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Tsegay BA, Gebreegziabher BG. 2019. Effects of terrains’ soil and altitude on performance of Abyssinian pea (Pisum sativum var. abyssinicum A.Braun) landraces of Ethiopia. Biodiversitas 20: 3467-3477. Pea production in Ethiopia is mainly located in the highlands. Field-based agronomic performance evaluation of Abyssinian pea landraces at different altitudes and soil types are rarely explored. This study was conducted to assess the effects of soil composition and altitude on morphological and yield traits of three landraces. The experimental investigation used was a completely randomized block design. Morphological and yield traits of the landraces considered in this study varied across agroecology. The variations were due to soil nutrient differences, altitude of the agroecology and their interactions. Soil samples collected from the mid-altitude had the highest pH of 7.71±0.07. Cation exchange capacity of this soil was found to be 45.46±0.71, in covenant with the approximate cation exchange capacity of most soils (>40 CEC meq/100 g soil) around neutral pH. This agroecology was found to be best for overall performance of the landraces. In the highland terrain, the landraces were less vigorous and shorter in height. In the lowland terrain, landraces were taller in height but gave low yield. Gedober 2017 landrace performed best in seed yield (6.00±0.11g/plant) and harvest index (0.32±0.43) at the mid-altitude. From this study, farmers are mindful to cultivate Gedober 2017 landrace at midland and highland pea production potential areas of Ethiopia.